Modeling Hybrid Renewable Energy Systems for Optimal Investment and Operational Decisions - Levy, Roberto; Brodsky, Alexander (SN computer science, 2022)
This paper focuses on making optimal investment and operational recommendations for a Hybrid Renewable Energy System (HRES). For this purpose, we develop a modular composite analytic performance model for HRES investment, which is based on an extensible library of atomic component models, including power storage, generators, renewable sources, third-party contracts, and household consumption. The performance model is able to formally express feasibility constraints and different key performance indicators, including total cost of ownership, environment impact, and infrastructure resilience, as a function of investment and operational decision variables. Based on the performance model, we design and develop a decision guidance system to enable actionable investment recommendations that optimize total cost of ownership, subject to the operational constraints associated with the network. We demonstrate the model in a case study for a municipal electric utility.